PENGARUH MODIFIKASI MEDIA PARALON TERHADAP HASIL BELAJARLEMPAR LEMBING PADA PESERTA DIDIK - Daris, Nandakanmahe; Haetami, Mimi; Hidasari, Fitriana Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem in this research is whether there is influence of paralon media modification to javelin learning result in class X student of Christian SMA Abdi Wacana Pontianak. The purpose of this study was to determine whether there was an influence of modification of paralon media on student learning outcomes.The population in this study is class X as many as 3 classes, amounting to 83 students. Sampling in this study uses purposive sampling technique, namely class X C, which amounts to 27 students. The method used in this research is experiment with pre-experimental design. Data analysis was done by computerization and analysis by using t-test.Based on result of t-test obtained bigger than ttable that is 11,419> 2,056 with significant level 5% and at degrees of freedom (db) 26 which mean there is influence of modification of paralon media to result of learn of javelin in student class X Christian SMA Abdi Wacana Pontianak. From the calculation of the mean shows that the posttest mean is greater than the mean pretest with a value of 8.33> 6.74. Standard Pretest Deviation of 0.712 and Standard deviation posttest of 0.679, which means that the error rate of learners is reduced and there is influence of paralon media modification on the results of learning javelin in class X students Christian SMA Abdi Wacana Pontianak.Â Keywords: Modification, Media, Learning Outcomes, Javelin.